Inverted (Reverse) Takotsubo Cardiomyopathy following Cerebellar Hemorrhage. (11th March 2014) - Piérard, Sophie; Vinetti, Marco; Hantson, Philippe
Abstract : Background . First described in 2005, inverted takotsubo is one of the four stress-induced cardiomyopathy patterns. It is rarely associated with subarachnoid hemorrhage but was not previously reported after intraparenchymal bleeding. Purpose . We reported a symptomatic case of inverted takotsubo pattern following a cerebellar hemorrhage. Case Report . A 26-year-old woman presented to the emergency department with sudden headache and hemorrhage of the posterior fossa was diagnosed, probably caused by a vascular malformation. Several hours later, she developed acute pulmonary edema due to acute heart failure. Echocardiography showed left ventricular dysfunction with hypokinetic basal segments and hyperkinetic apex corresponding to inverted takotsubo. Outcome was spontaneously favorable within a few days. Conclusion . Inverted takotsubo pattern is a stress-induced cardiomyopathy that could be encountered in patients with subarachnoid hemorrhage and is generally of good prognosis. We described the first case following a cerebellar hematoma.